THE APPLICATION OF AI-POWERED AND DIGITAL TOOLS IN TEACHING VOCABULARY - Saroyan, Satenik (Foreign Languages for Special Purposes, 2025)
This paper aims at highlighting the importance of incorporating some digital and AI tools in the process of teaching vocabulary. Traditional methods will always remain at the core of teaching, however, with the development of new technologies, teachers also need to change their approaches and methods by incorporating digital activities into their course. This helps to attract the attention of the new generation that has grown on digital tools. Although teachers often do not warmly welcome the application of AI tools by the side of learners and continue to recommend them not to rely on artificial intelligence for fulfilling their tasks, students continue to widely apply them for their curricular activities. It increasingly becomes impossible to stop learners from using those tools in their study. Thus, teachers have no other choice than to make this challenge into a chance. For doing this, teachers could elaborate relevant approaches to include these modern-day tools in their lesson planning and to transform their teaching methods according to the new tendencies.The research was carried out by the application of the experimental method to foster student engagement and to provide our study with practical value, as well as with empirical evidence. This method also helped us create proper conditions for students to apply the newly acquired knowledge in practice.The results and findings discussed in this research have shown that the application of AI-powered tools in teaching vocabulary can lead to effective and active teaching in different educational institutions. Moreover AI-powered digital tools help the teacher choose certain tasks and vocabulary levels according to the individual needs of every learner, which provides the course with effectiveness and raises its productivity.
Keywords: generate wordlists; vocabulary assimilation; AI-powered tools; vocabulary retention; active method; word quiz; individual needs; student engagement